Advances in a DSL to Specify Smart Contracts for Application Integration Processes - Dornelles, Eldair F.; Parahyba, Fernando; Frantz, Rafael Z.; Roos-Frantz, Fabrícia; Reina-Quintero, Antonia M.; Molina-Jiménez, Carlos; Bocanegra, José; Sawicki, Sandro (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
Several languages have been developed for writing smart contracts for specific domains, such as health, finance, and business processes. However, none of them includes the constructors needed for writing smart contracts used in application integration processes which have their own particularities. Such smart contracts are responsible for monitoring the communication between the process and the applications to guarantee that the rights of the parties involved in the integration process are observed. To cover the gap, this paper discusses a domain-specific language for writing smart contracts in the application integration domain. It provides constructors to write smart contracts with a level of abstraction close to the natural language used in conventional contracts.